PENGARUH”RETURN ON ASSET, CURRENT RASIO DAN DEBT TO EQUITY RASIO TERHADAP HARGA SAHAM PT. SIDOMUNCUL TBK - Siti Zubaidah; Sunartiyo (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
Stock prices, namely prices that occur on the stock exchange at a certain time, can change up or down in a very fast matter of time, either in minutes to second. Stock prices are usually influenced by supply and demand. If shares occur in the capital market, the more investors who buy shares from a company, the share price of that company will increase. The purpose of this study was to determine how the influence of return on asset, current ratio and debt to equity ratio on stock prices at PT. Sidomuncul Tbk. The method in this study uses quantitative methods with the sampling technique is purposive sampling. The data analysis technique used is the classical assumption test and hypothesis testing. determination test. The results of the study show that simultaneously and partially the return on assets, current ratio and debt to equity have an effect on the stock price of PT. Sidomuncul, tbk.